2014
DOI: 10.1074/jbc.m114.569814
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput Analysis of Ultrasonication-forced Amyloid Fibrillation Reveals the Mechanism Underlying the Large Fluctuation in the Lag Time

Abstract: Background: Ultrasonication effectively breaks supersaturation and forces amyloid fibrillation. Results: A high-throughput analysis of amyloid fibrillation showed that, although the lag time varied depending on the conditions, its coefficient of variation was constant. Conclusion: The large fluctuation in the lag time originates from a process associated with a common amyloidogenic intermediate. Significance: High-throughput analysis is powerful enough to clarify the mechanisms of supersaturation-limited phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 38 publications
2
55
0
Order By: Relevance
“…These ultrasonic power-dependent decreases in the lag time and ThT fluorescence (Fig. 2C) were consistent with our previous studies on ␤2m (22,25) and findings on ␣-synuclein fibrils (27) and amyloid ␤-(1-40) fibrils (26), implying that extensive ultrasonication transformed the preformed fibrils to amorphous aggregates. In addition, the decrease observed in maximal ThT fluorescence with an increase in ultrasonic power suggested the direct formation of amorphous aggregates as well as amyloid fibrils.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…These ultrasonic power-dependent decreases in the lag time and ThT fluorescence (Fig. 2C) were consistent with our previous studies on ␤2m (22,25) and findings on ␣-synuclein fibrils (27) and amyloid ␤-(1-40) fibrils (26), implying that extensive ultrasonication transformed the preformed fibrils to amorphous aggregates. In addition, the decrease observed in maximal ThT fluorescence with an increase in ultrasonic power suggested the direct formation of amorphous aggregates as well as amyloid fibrils.…”
Section: Resultssupporting
confidence: 80%
“…The decrease in ThT fluorescence was accelerated when the lag time was shorter, suggesting that this reduction was caused by the ultrasonication-dependent transformation of preformed fibrils into distinct conformational states (22,25,26). Combined with the salt concentration-dependent competition between fibrillation and amorphous aggregation, we showed that a competitive mechanism, in which various amyloidogenic and non-amyloidogenic aggregates competed (Fig.…”
mentioning
confidence: 87%
See 3 more Smart Citations